WHY VILLAGE FUND NOT YET PROMOTING ENVIRONMENTAL SUSTAINABILITY? AN EMPIRICAL STUDY OF VILLAGE FUND INCENTIVES IN CENTRAL JAVA PROVINCE, INDONESIA - Wida Astuti; Djuwityastuti .Djuwityastuti (Yustisia, 2018)
One of the purposes of granting village funds under Village Law Number 6 year 2014 is to support the rural development through the sustainable use of natural and environmental resources. Based on the statistical data from The Ministry of Finance Republic of Indonesia, the grant of village funding since 2015 has increased for each year. However, based on empirical data in The Central Java Province is still in the allocation for physical development (infrastructure sector) and far from environmental sustainability programs. Through research funded by Sebelas Maret University Surakarta, this article will describe (1) factors that hinder the sustainable environmental development and (2) how the way out that can be applied to support sustainable environmental development for subsequent years.